1995
DOI: 10.1093/oxfordjournals.aje.a117721
|View full text |Cite|
|
Sign up to set email alerts
|

The Frequency of Idiopathic Parkinson's Disease by Age, Ethnic Group, and Sex in Northern Manhattan, 1988–1993

Abstract: Sex and ethnic differences in the frequency of Parkinson's disease have become increasingly important, because putative genetic and environmental risk factors have been identified. The authors estimated the prevalence and incidence of Parkinson's disease in a culturally diverse community in New York City over a 4-year period (January 1, 1988-December 31, 1991) using a disease registry substantiated, for older individuals, by a subsequent survey of a random sample of Medicare recipients between January 1, 1992,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
229
7
15

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(275 citation statements)
references
References 0 publications
24
229
7
15
Order By: Relevance
“…18 Although each of these paradigms has provided useful information for the understanding of Parkinson's disease, they share a significant limitation namely, that the neurological lesions they study are caused by experimental manipulations rather than by aging, the only unequivocal risk factor for Parkinson's disease. 19,20 In this context, the aging female rat emerges as a unique model of spontaneous and progressive age-related DA dysfunction. Besides, the functional status of TIDA neurons can be readily monitored in the animals by measuring circulating PRL levels.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although each of these paradigms has provided useful information for the understanding of Parkinson's disease, they share a significant limitation namely, that the neurological lesions they study are caused by experimental manipulations rather than by aging, the only unequivocal risk factor for Parkinson's disease. 19,20 In this context, the aging female rat emerges as a unique model of spontaneous and progressive age-related DA dysfunction. Besides, the functional status of TIDA neurons can be readily monitored in the animals by measuring circulating PRL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported lower prevalence of PD in Africa [21,40,[71][72][73], Asia [32,46,62,[65][66][67]74] and South America [63,64] compared to Europe [16,17,19,22,25,58,60,61,75]. To facilitate comparison among 25 studies conducted in different countries, Zhang et al [76] calculated age-standardized prevalence proportions using the US population in 1970 as the standard.…”
Section: Diagnosis Of Pdmentioning
confidence: 99%
“…In fact, the crude prevalence of PD in Africa is lowest in the eastern and western countries, where life expectancy is lowest, whereas prevalence proportions in northern African countries [78,79] are similar to those in developed countries [80]. Another suggested explanation for the low prevalence in Africa is that hospital-based ascertainment used in some studies [40,[71][72][73] may be biased by socioeconomic and cultural factors [77].…”
Section: Diagnosis Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Disse forstyrrelser omfatter f.eks. Parkinsons syge, som også i højere grad rammer maend end kvinder (Mayeux et al 1995, Van Den Eeden et al 2003.…”
Section: Stammenunclassified